Laser Based Real Time Antenna Pointing Measurement System - Kumar, Anish; N, Thangadurai (International Journal of Engineering and Technology, 2018)
The antenna pointing system is very important to obtain an optimum received signal level. To achieve it, presenting the implication of laser beam radiated emission requirements and how they state for pointing measurement system, its impact on design, verification and testing for the antenna pointing system. The antenna pointing system is developed by using array of linear light sensors, crosshair laser weapon, where the light sensors are mounted on the board and laser weapon putted on the antenna mechanism. On the rotator system, composed by using 2 gears and 2 DC motors with customized frames. For collecting the sensors data using ProASIC3 FPGA fabric and finding the numbers and which sensors has been active during the emitting period and 32-bit ARM Cortex-M3 processor take account into the pointing measurement system to computing the pointing and pointing error. At the end, the final step is building a User Graphical Interface on PC to show the output of the antenna pointing. Â Â